Monitoring South American Tomato Leaf Miner, Tuta absoluta (Meyrick) and Assessment of Management Practices Adopted in Kavre, Nepal - Gautam, Samikshya; Adhikari, Debraj; Sapkota, Bala R.; Shrestha, Arjun K. (Journal of the Plant Protection Society, 2018)
The study was carried out from April-August, 2017 to monitor the population of Tuta absoluta and to assess the management practices being adopted in Kavre, Nepal. Study consisted of two major parts: monitoring of insect population and farmer’s survey. The population of T. absoluta ranged from 51 to 972 in each Wota -T trap. The highest population of the insect in traps were recorded in Dhulikhel followed by Panauti and Banepa. Majority of tomato growers (78%) reported T. absoluta as the most problematic among other pests, diseases and disorders. The data from E-Plant clinic at Panchkhal revealed the degree of severity of T. absoluta in tomato crop. Tomato growers have adopted cultural, physical, mechanical, para-pheromone lures, quarantine, botanical and chemical methods for the management of this pest. Majority of them relied on chemical pesticide (94%) followed by cultural practices (86%) and Tomato Leaf Miner (TLM) lure (66%) based on cumulative percentage of respondents. Use of TLM lure was found as the best in terms of its effectiveness, safety, and practicability. Thus, Integrated Pest Management strategies are essential to limit the significant loss and reduce dependency on chemical pesticides in future.